(untitled) (Fiep Bulletin - online, 2014)
Chemotherapy is the cytotoxic substance use in of the cancer. The teams that work in the preparation and applications of chemotherapy drugs need continued improvement. The present study it has for objective to describe action of nursing for patients submitted to the chemotherapy treatment. For in such a way, it was opted to the Bibliographical Research. The chemotherapy is commonly toxic for innumerable normal cells of the organism (marrow bone and mucosa in general) and its indication implies in a series of factors that must be taken in account in its planning, such as: the age of the patient, its nutritional state, and pulmonary, renal, hepatic function, the presence of infection, the type of tumor, the existence of metastasis and its extension. It is basic that, beyond its paper technician related with the manuscript of the drugs, the nurse acts as a multiplier of information correct regarding the chemotherapy treatment, wasting doubts and undoing taboos. The knowledge of the reactions and complications during the chemotherapy treatment if makes necessary so that if the can have subsidies to give assistance of adequate nursing to these patients, aiming at to the improvement in the quality of life, many times preventing possible decurrent complications of the treatment.